PERAN SETTING ELEMEN FISIK TERHADAP AKTIVITAS PADA KAMPUNG WISATA OBJEK STUDI: KAMPUNG LAWAS MASPATI DAN KAMPUNG PELANGI KENJERAN SURABAYA - Dionisius Arief Anjasmoro; Yohanes Basuki Dwisusanto (Riset Arsitektur (RISA), 2022)
Abstract - Indonesia has a variety of urban tourism village scattered in various regions. The tourism village has various themes according to the character of the are and the residents of the village. Such as Batik Village, Ceramic Village, Rainbow Village, etc. The presence of the concept of an urban tourism village doesn not only occur in Indonesia, but also occurs in various other countries such as Gamcheon Culture Village in Korea, Chefchaouen in Marocco, Marsaxlokk Village in Malta, etc. With the presence of the concept of tourism village, it provides novelty for both humans (tourist and villagers) as the users of space accompanied by their activities. Based on these problems the authors are interested in conducting this research. This research will discuss about what is meant by a tourist village, how tourism activities occur in the two study objects and how architecture as a physical element plays a role in the activities in it. The purpose of this study is to describe how far a village called a tourist village is feasible as a tourist place by introducing the tourism criteria, what are the criteria for a village to be called a tourist village. This research is a descriptive qualitative research, using Kampung Lawas Maspati and Kampung Pelangi Kenjeran as objects of study to be compared based on the tourism criteria itself, to further examine how the physical (architectural) element settings play a role in accommodating tourism activities in the village itself. So that how far the two objects of study meet the existing tourist criteria so that they are feasible as tourist attractions. With this research, it is hoped that it can provide an understanding of what is meant by a tourist village and the importance of the role of architecture in realizing the tourism village it deserves. The results of the research show that the physical elements in Kampung Lawas Maspati meet the three criteria that a tourism village needs to have and there are tourism activities organized by local village managers, while Kampung Pelangi Kenjeran has not fulfilled existing tourism criteria, the availability of physical elements in Kampung Pelangi Kenjeran is very minimal. This proves that the term "tourism" in Pelangi Kenjeran village is still not appropriate as it should be. Key Words: setting, physical elements, activity, urban tourim village